2016
DOI: 10.4103/0971-9784.179633
|View full text |Cite
|
Sign up to set email alerts
|

Serum albumin perturbations in cyanotics after cardiac surgery: Patterns and predictions

Abstract: Introduction:Hypoalbuminemia is a well-recognized predictor of general surgical risk and frequently occurs in patients with cyanotic congenital heart disease (CCHD). Moreover, cardiopulmonary bypass (CPB)-induced an inflammatory response, and the overall surgical stress can effect albumin concentration greatly. The objective of his study was to track CPB-induced changes in albumin concentration in patients with CCHD and to determine the effect of hypoalbuminemia on postoperative outcomes.Materials and Methods:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 27 publications
1
11
0
3
Order By: Relevance
“…Like the few other studies in the literature that evaluated the association of serum albumin levels on the outcomes in this population, 6,7 we found that post-operative hypoalbuminemia had a univariate association with morbidity. However, in this multi-centre cohort of predominantly neonates, there was no independent association between post-operative hypoalbuminemia and morbidity, despite the larger sample size.…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…Like the few other studies in the literature that evaluated the association of serum albumin levels on the outcomes in this population, 6,7 we found that post-operative hypoalbuminemia had a univariate association with morbidity. However, in this multi-centre cohort of predominantly neonates, there was no independent association between post-operative hypoalbuminemia and morbidity, despite the larger sample size.…”
Section: Discussionsupporting
confidence: 66%
“…3,4 Few studies have evaluated the impact of hypoalbuminemia in children with cardiac disease. [5][6][7] In a mixed cohort of adult and paediatric cardiac surgical patients, albumin level decreased after cardiopulmonary bypass and was associated with post-operative morbidity and mortality. 6 Leite et al 7 demonstrated in 30 paediatric cardiac surgical patients that pre-and post-operative albumin <3 g/dl has a univariate association with mortality, postsurgical infection, and longer length of hospital stay.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Malnutrition is an important factor that regulates albumin production; however, serum albumin is also affected by various non-nutritional factors, such as chronic inflammation, repeated infections, liver failure, renal insufficiency, gastrointestinal function changes, and fluid overload dilution (10). Studies have shown that albumin is also decreased in IE patients (11), and the cause is not only malnutrition but also inflammation, infection, and renal insufficiency.…”
Section: Introductionmentioning
confidence: 99%
“…It is made from blood donor plasma and functions as a physiological plasma expander. This product is created using the alcohol fractionation process, and infectious pathogens are rendered inactive by heating it to 60 °C for 10 hours [1][2] . Human albumin possesses osmotic or oncotic characteristics, which is the primary basis for its therapeutic use, and it raises plasma volume similarly to crystalloid and colloidal solutions.…”
Section: Introductionmentioning
confidence: 99%